Digital inclusive finance and enterprise innovation: Empirical evidence from Chinese listed companies - Mingzhao Xiong; Wenqi Li; Brain Teo Sheng Xian; Ao Yang (Journal of Innovation & Knowledge (JIK), 2023)
The development of Digital Inclusive Finance (DIF) offers new opportunities for corporate innovation. This study empirically explores the influence of DIF on firms' R&D and innovation output via a two-way fixed-effects model and an instrumental variable method using the 2011-2018 Peking University Digital Financial Inclusive Index to match city-level data of A-share listed companies. The results show that DIF plays a positive role in boosting company R&D innovation. Among the three DIF sub-dimensions, DIF coverage is the most significant in promoting R&D innovation. The role of DIF in promoting corporate R&D and innovation is most prominent for private enterprises, small and medium-sized enterprises, secondary and tertiary industries, and high-growth enterprises. In addition, DIF helps foster enterprise R&D innovation and can gratify the desire for innovation felt by adventurous business owners. Further analysis reveals that internal financing constraints and external banking competition have intermediary effects on the promotion of enterprise innovation, which are observed for the three sub-dimensions of DIF. The results of an instrumental variable regression and other robustness tests confirm the main findings.
Keywords: 650; Digital inclusive finance; Enterprise innovation; Entrepreneur risk-taking spirit; Financing constraint